Efek Materi Belajar dan Adopsi Inovasi Terhadap Pengetahuan Petani Tentang Kependudukan Lingkungan Hidup di Kota Sengeti Jambi (Universitas Esa Unggul, 2006)
AbstractThe aim of this study is to assess the impact a of learning materials and farmer adoption of innovations on the knowledge of population and environmental in sengeti Jambi. The technique for assigning the treatment to the learning groups was random. Sample for analyzing data were 120 PPL (Penyuluh Pertanian Lapangan). He result of the research indicate four findings: (1) for the whole farmer, the knowledge of learners who taught by the learner controlled learning material = ; is very significantly higher than those who taught by the institutionally controlled learning material ; (2) the knowledge of farmer earlier adoption who taught by the learner controlled learning material is verv significantly higher than those a who taught by the institutionaly controlled learning material ; (3) the knowledge of later adopters who taught by the learner controlled learning material ; does not differ significantly from those who taught by the institutionally controlled learning material ; (4) there is a significant effect of the two variables on the learner's knowledge. Therefore, the recommended policy is mass literacy development on environment that generates a population is aware of the environment and is associated problems.Keywords: Farmer Adoption,Learning Material, Institutional